TINJAUAN ASPEK TEKNIS PEMILIHAN MEDIA BIOFILTER UNTUK PENGOLAHAN AIR LIMBAH - Said, Nusa Idaman; Marsidi, Ruliasih (Jurnal Air Indonesia, 2005)
There are literally dozens of different types of biofilters used for wastewater treatment applications. While many have common features, some are fundamentally different from the rest. The purpose of this article is to educate the reader about the types of packings used for fixed film biofilters.The types of biofilters under discussion are filters that employ a non-moving surface area to provide a substrate for various bacteria to attach and grow. The substrate remains in place while the water flows through the system. The heart of these biofilters is the packing or media used to provide the surface area. The type of packing used strongly influences both the capital and operating costs of the biofilter. It is important to emphasize however, that the packing merely provides surface area for bacteria to colonize. It is the bacteria that do the actual work of the biofilter. In order for the bacteria to do their job effectively, the biofilter and packing design must provide an even distribution of nutrients and oxygen while removing dissolved and suspended waste products. Most biofilters utilize aerobic bacteria but it is also possible to design and operate anaerobic systems for special purposes. Various types of packings exist for fixed film biological filters. Each different type has advantages and disadvantages but in terms of overall cost and suitability, the structured packings are the best choice for commercial biofilter designs.Ã‚Â Kata kunci : biofilter, media, pengolahan air limbah.